Antioxidants Reduce Muscular Dystrophy in the dy2J/dy2J Mouse Model of Laminin α2 Chain-Deficient Muscular Dystrophy - Vahid M. Harandi; Bernardo Moreira Soares Oliveira; Valérie Allamand; Ariana Friberg; Cibely C. Fontes-Oliveira; Madeleine Durbeej (MDPI AG, 2020)
Congenital muscular dystrophy with laminin α2 chain-deficiency (LAMA2-CMD) is a severe neuromuscular disorder without a cure. Using transcriptome and proteome profiling as well as functional assays, we previously demonstrated significant metabolic impairment in skeletal muscle from LAMA2-CMD patients and mouse models. Reactive oxygen species (ROS) increase when oxygen homeostasis is not maintained and, here, we investigate whether oxidative stress indeed is involved in the pathogenesis of LAMA2-CMD. We also analyze the effects of two antioxidant molecules, N-acetyl-L-cysteine (NAC) and vitamin E, on disease progression in the dy2J/dy2J mouse model of LAMA2-CMD. We demonstrate increased ROS levels in LAMA2-CMD mouse and patient skeletal muscle. Furthermore, NAC treatment (150 mg/kg IP for 6 days/week for 3 weeks) led to muscle force loss prevention, reduced central nucleation and decreased the occurrence of apoptosis, inflammation, fibrosis and oxidative stress in LAMA2-CMD muscle. In addition, vitamin E (40 mg/kg oral gavage for 6 days/week for 2 weeks) improved morphological features and reduced inflammation and ROS levels in dy2J/dy2J skeletal muscle. We suggest that NAC and to some extent vitamin E might be potential future supportive treatments for LAMA2-CMD as they improve numerous pathological hallmarks of LAMA2-CMD.